Pengukuran Somatotype dan Center of Pressure (CoP) dengan Force Platform untuk Mengetahui Pengaruh Morfologi Tubuh terhadap Keseimbangan Postur Berdiri - Susanti, Hesty; Mukhtar, Husneni; Rahmawati, Dien; Arik Geraldy Fauzi, Muhammad; Setiyadi, Suto (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2022)
The human ability to carry out daily activities is influenced by the balance of body posture in various positions, especially in a standing position. One of the factors of body balance is a biomechanical factor which is influenced by the morphology of the human body. Somatotype is a method of classifying the morphology of the human body, while the balance of human body posture can be measured based on the center of pressure (COP), which is the center of pressure generated when humans stand up. In this study, a system was designed to classify somatotypes using the Heath-Carter formula and assessment of body posture balance. Somatotype grouping is done with inputs in the form of body height measured with an ultrasonic sensor, body mass measured using a set of load cells to determine body mass index (BMI), and 8 anthropometric parameters. While the measurement of body balance is carried out by measuring the COP values using 8 load cell sensors. Eight anthropometric parameters were used, namely skin folds in the triceps, subscapular, supraspinal, and medial calf areas, the width of the femur and humerus bones, and the triceps and calf circumference. Statistical parameter values ​​in the form of mean, range, and approximate entropy (ApEn) are then calculated from the obtained COP values, i.e., for the medial-lateral (ML) and anterior-posterior (AP) directions, so that the center point of the COP, the displacement distance of each axis (ML and AP directions), and their stability can be determined. The measurement results are grouped and combined to display the type of somatotype associated with the COP value to obtain a relationship between the type of somatotype and a person's standing posture. Measurements were carried out on 14 male subjects with an age range of 15-23 years. The measurement results show an average error range of 0.37-2.58% for ultrasonic sensors, 0.64-4.67% for load cells, 0.1-0.6% for ApEn values ​​at COP in the medial-direction direction (ML COP), and 0% for ApEn in COP in the anterior-posterior direction (AP COP). The average difference range for ML COP is 0.03-0.84 cm, while the average for AP COP is 0.14-0.58 cm. These differences indicate a shift in the center of pressure on the subject's body when measurements are taken compared to the original state. The ectomorphic somatotype group had the greatest instability compared to 2 other somatotype groups, namely endomorphic and mesomorphic. In each somatotype group, the value of the AP COP range which is greater than in the ML COP indicates a greater tendency of body sway in the anterior-posterior direction. Keywords: somatotype; balance posture; center of pressure; body morphology